2017
DOI: 10.1002/ags3.12018
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of recurrent intrahepatic cholangiocarcinoma: predictors, adjuvant chemotherapy, and surgical therapy for recurrence: A multi‐institutional study by the Kyushu Study Group of Liver Surgery

Abstract: Objectives of the present study were to identify predictors of the recurrence of intrahepatic cholangiocarcinoma (ICC), and to evaluate the survival benefit of adjuvant chemotherapy and surgical treatment for ICC recurrence. A multi‐institutional retrospective study was carried out in 356 patients with ICC who underwent curative surgery at one of 14 institutions belonging to the Kyushu Study Group of Liver Surgery. A total of 214 patients (60%) had recurrence. Predictors of ICC recurrence were as follows: posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
(44 reference statements)
5
26
0
3
Order By: Relevance
“…These authors showed that tumour diameter of 5 cm or less was significantly associated with longer recurrence-free survival, but this association was lost in the multivariable analysis. It was shown that a median tumour diameter of 5 cm or more could independently predict both poor OS and DFS, in line with the findings from more recent cohorts 19,20 . Using SEER (Surveillance, Epidemiology and End Results) data, it has been shown 22 that node positivity is associated with worse survival in patients with cholangiocarcinoma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These authors showed that tumour diameter of 5 cm or less was significantly associated with longer recurrence-free survival, but this association was lost in the multivariable analysis. It was shown that a median tumour diameter of 5 cm or more could independently predict both poor OS and DFS, in line with the findings from more recent cohorts 19,20 . Using SEER (Surveillance, Epidemiology and End Results) data, it has been shown 22 that node positivity is associated with worse survival in patients with cholangiocarcinoma.…”
Section: Discussionsupporting
confidence: 82%
“…These cohorts, however, lack sufficient numbers of patients to be able to define precisely the role of surgery, as well as that of additional therapy, in recurrent ICC. The present cohort of patients with recurrent ICC undergoing repeat surgery with curative intent was almost as large as that from two recent multi-institutional studies 18,20 . Furthermore, the results of the present study are similar to the findings of Si and colleagues 18 , who reported on the largest cohort of patients (72) undergoing repeat liver resection, in which the median OS time was 45⋅1 months with a 1-year survival rate of 97 per cent.…”
Section: Discussionmentioning
confidence: 94%
“…Guidelines for the management of recurrent ICC remain controversial and poorly defined. In the routine clinical practice, the therapeutic strategy for recurrence was evaluated based on tumor location, number of tumors, general patient condition, and liver function (20)(21)(22); however, the final choice was influenced by patient factors, including the preference for less invasive treatment and financial considerations decided by our MDT. The treatment allocation for recurrent ICC is recognized as a significant factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of treatment for recurrence was determined from the characteristics of the recurrent tumor, patient preference, and discussion among our multidisciplinary team (MDT) (19)(20)(21). Treatment with curative intent, including surgical re-resection and ablation, was performed in patients with solitary intrahepatic recurrence without a portal vein tumor thrombus, and in patients with an extrahepatic recurrence for which curative treatment was feasible (20)(21)(22). Other treatments were individualized for patients with advanced recurrent disease and included transarterial chemoembolization (TACE), chemotherapy and radiotherapy, depending on disease extent and the patient's performance status.…”
Section: Treatment Of Recurrencementioning
confidence: 99%
“…Although iCCA is a relatively infrequent entity, alarming rises in iCCA incidence and iCCA‐related mortality have been reported worldwide over the past few decades . In addition, surgical resection and transplantation remain the only potentially curative approaches, and limited chemotherapeutic treatment options and frequent treatment resistance are unduly prominent in patients with iCCA . Hence, the iCCA prognosis continues to be pessimistic, with a 5‐year survival rate of <10%, and rapid, fatal deterioration.…”
Section: Introductionmentioning
confidence: 99%